The Impact of Technical Knowledge on Increasing the Efficiency and Effectiveness of Accounting Information Systems in Banks: An Analytical Study in a Selected Sample of Iraqi Banks - Hashim ALSaqa, Zeyad; Abbas Khudhur, Fadhil (Journal of Research in Finance and Accounting, 2022)
The study dealt with a topic of great importance at the present time in light of the continuous changes and developments in the information technology environment and the expansion of its use in various sectors, including the business sector in which accounting information systems operate. The problem of the study is to determine the effect of technical knowledge on increasing the efficiency and effectiveness of accounting information systems in banks. The study's goal was to clarify the concept of technical knowledge and the importance of it in the work of accounting information systems, with support coming from an exploratory study of a selected sample of Iraqi banks that used information technologies in their accounts.Various activities, including the work of accounting information systems. One of the results of the study is that there are many uses of information technologies in accounting information systems in the study community, which is represented by a selected sample of Iraqi banks, and the study sample realizes the importance of using these means in the work of accounting information systems and that their use can contribute to enhancing the efficiency and effectiveness of accounting information systems. The study also recommended the need to provide technical knowledge through academic study, practical experience, continuing education, and participation in training courses to identify new uses and updates of various means in the work of accounting information systems.